A Study on the Existing Status and the problems of Primary Education with Special Reference Sivsagar District, Assam - Gitashree Gogoi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Primary education is the base or foundation of the education system where a child gets the basic education of his or her life. Every child’s born in this world with some innate potentialities or abilities which differ from each others. According to John Locke “a child is born a blank state and its later behavior is shaped by experience”. Primary education provides the first place where a child builds his or her self esteem. It is the right place for the child’s foundation for lifelong progress. The main objective of the study is to find out the existing status with respect to infrastructure facilities, method of teaching, and medium of instruction, curricular or co-curricular activities. Also to find out the problems of Primary education and to provides some suggestions for the improvement of primary education. The method used for the present study is descriptive survey method. The study revealed that existing status of primary education is not good and in this regards some suggestions are provided for the development and improvement of pre-primary Education. Parents role is utmost important in this period of life as they are the first teacher through the child learn ideals and proceeds socialization. Teachers must give equal attention to the children to the children and motivate them to take part different activities that will help them learn new thing in life.